Nocturnal mosquito Cryptochrome 1 mediates greater electrophysiological and behavioral responses to blue light relative to diurnal mosquito Cryptochrome 1 - Au, David D.; Liu, Jenny C.; Nguyen, Thanh H.; Foden, Alexander J.; Park, Soo Jee; Dimalanta, Mia; Yu, Zhaoxia; Holmes, Todd C. (Frontiers in Neuroscience, 2022)
Nocturnal Anopheles mosquitoes exhibit strong behavioral avoidance to blue-light while diurnal Aedes mosquitoes are behaviorally attracted to blue-light and a wide range of other wavelengths of light. To determine the molecular mechanism of these effects, we expressed light-sensing Anopheles gambiae (AgCRY1) and Aedes aegypti (AeCRY1) Cryptochrome 1 (CRY) genes under a crypGAL4-24 driver line in a mutant Drosophila genetic background lacking native functional CRY, then tested behavioral and electrophysiological effects of mosquito CRY expression relative to positive and negative CRY control conditions. Neither mosquito CRY stops the circadian clock as shown by robust circadian behavioral rhythmicity in constant darkness in flies expressing either AgCRY1 or AeCRY1. AgCRY1 and AeCRY1 both mediate acute increases in large ventral lateral neuronal firing rate evoked by 450 nm blue-light, corresponding to CRY’s peak absorbance in its base state, indicating that both mosquito CRYs are functional, however, AgCRY1 mediates significantly stronger sustained electrophysiological light-evoked depolarization in response to blue-light relative to AeCRY1. In contrast, neither AgCRY1 nor AeCRY1 expression mediates measurable increases in large ventral lateral neuronal firing rates in response to 405 nm violet-light, the peak of the Rhodopsin-7 photoreceptor that is co-expressed in the large lateral ventral neurons. These results are consistent with the known action spectra of type 1 CRYs and lack of response in cry-null controls. AgCRY1 and AeCRY1 expressing flies show behavioral attraction to low intensity blue-light, but AgCRY1 expressing flies show behavioral avoidance to higher intensity blue-light. These results show that nocturnal and diurnal mosquito Cryptochrome 1 proteins mediate differential physiological and behavioral responses to blue-light that are consistent with species-specific mosquito behavior.